Effects of Chitosan in Extending the Vase Life of Cut Chrysanthemum (Dendranthema Morifolium Ramat) Flowers - Azian, Eddy (2006)
The effect of the isolated bacteria strains on the vase life of cut flowers of Chrysanthemum (Dendranthema morifolium Ramat) was investigated. The bacteria strains were isolated from the cut stem end and vase water of cut chrysanthemum flowers. The longevity of vase life and total water uptake of cut s I chrysanthemum was reduced by placing the stems in a suspension of Pantoea' agglomerans and Burkholderia rnultivorans at 10' CFU m ~ " . The study was also conducted to look at the effects of chitosan in extending the vase life of cut chrysanthemum. Chitosan was applied as pulse treatment. Cut flowers were treated with 1) chitosan at 0, 25, 50, 75 and 100 mg L-', 2) chitosan at concentration 1) iubplemented with 2% sucrose, 3) chitosan at concentration 1) supplemented with 1.5 mM Ca(NO& and 4) chitosan at concentration 1) supplemented with 1.5 mM Ca(NO& and 2% sucrose. The experiment was carried out in the Postharvest Laboratory with the environmental conditions, 25 * 2OC, 70% RH and 15 ymol m-2 s-' light intensity from cool-white fluorescent lamps for 12 hours. Compared to those held in control, all treatments extended the vase life. Treatment 75 mg L-' chitosan supplemented with 1.5 mM Ca(NO& was the most effective in extending the vase life.